Evaluation of up-converting phosphor technology-based lateral flow strips for rapid detection of Bacillus anthracis Spore, Brucella spp., and Yersinia pestis. - Pingping Zhang; Xiao Liu; Chengbin Wang; Yong Zhao; Fei Hua; Chunfeng Li; Ruifu Yang; Lei Zhou (PLoS ONE, 2014)
Bacillus anthracis, Brucella spp., and Yersinia pestis are zoonotic pathogens and biowarfare- or bioterrorism-associated agents that must be detected rapidly on-site from various samples (e.g., viscera and powders). An up-converting phosphor technology-based lateral flow (UPT-LF) strip was developed as a point-of-care testing (POCT) to satisfy the requirements of first-level emergency response. We developed UPT-LF POCT to quantitatively detect the three pathogens within 15 min. Sample and operation-error tolerances of the assay were comprehensively evaluated. The sensitivity of UPT-LF assay to bacterial detection reached 10(4) cfu · mL(-1) (100 cfu/test), with a linear quantitative range of 4 to 6 orders of magnitude. Results revealed that the UPT-LF assay exhibited a high specificity with the absence of false-positive results even at 10(9) cfu · mL(-1) of non-specific bacterial contamination. The assay could tolerate samples with a wide pH range (2 to 12), high ion strengths (≥ 4 mol · L(-1) of NaCl), high viscosities (≤ 25 mg · mL(-1) of PEG20000 or ≥ 20% of glycerol), and high concentrations of bio-macromolecule (≤ 200 mg · mL(-1) of bovine serum albumin or ≥ 80 mg · mL(-1) of casein). The influence of various types of powders and viscera (fresh and decomposed) on the performance of UPT-LF assay was determined. The operational error of liquid measurement exhibited few effects on sensitivity and specificity. The developed UPT-LF POCT assay is applicable under field conditions with excellent tolerance to sample complexity and operational error.